Effects of D‐amino acid oxidase inhibition on memory performance and long‐term potentiation in vivo. Issue 1 (1st October 2013) - Hopkins, Seth C.; Campbell, Una C.; Heffernan, Michele L. R.; Spear, Kerry L.; Jeggo, Ross D.; Spanswick, David C.; Varney, Mark A.; Large, Thomas H.
Abstract N‐methyl‐d‐aspartate receptor (NMDAR) activation can initiate changes in synaptic strength, evident as long‐term potentiation (LTP), and is a key molecular correlate of memory formation. Inhibition of d‐amino acid oxidase (DAAO) may increase NMDAR activity by regulating d‐serine concentrations, but which neuronal and behavioral effects are influenced by DAAO inhibition remain elusive. In anesthetized rats, extracellular field excitatory postsynaptic potentials (fEPSPs) were recorded before and after a theta frequency burst stimulation (TBS) of the Schaffer collateral pathway of the CA1 region in the hippocampus. Memory performance was assessed after training with tests of contextual fear conditioning (FC, mice) and novel object recognition (NOR, rats). Oral administration of 3, 10, and 30 mg/kg 4H‐furo[3, 2‐b]pyrrole‐5‐carboxylic acid (SUN) produced dose‐related and steady increases of cerebellum d‐serine in rats and mice, indicative of lasting inhibition of central DAAO. SUN administered 2 h prior to training improved contextual fear conditioning in mice and novel object recognition memory in rats when tested 24 h after training. In anesthetized rats, LTP was established proportional to the number of TBS trains. d‐cycloserine (DCS) was used to identify a submaximal level of LTP (5× TBS) that responded to NMDA receptor activation; SUN administered at 10 mg/kg 3–4 h prior to testing similarly increased in vivo LTP levels compared to vehicle control animals. Interestingly, in vivo administration of DCS also increased brain d‐serine concentrations. These results indicate that DAAO inhibition increased NMDAR‐related synaptic plasticity during phases of post training memory consolidation to improve memory performance in hippocampal‐dependent behavioral tests.